Arbetsmiljö för djursjukskötare på ett smådjurssjukhus : inriktat på belastningsergonomi - Billing, Martina (SLU/Dept. of Animal Environment and Health (until 231231), 2013)
Purpose: The aim of this study was to observe and describe the work environment of veterinary nurses, focused on fysical ergonomics, in a Small Animal hospital.